On the equivalence of pre-Schröder equations - Józef Kalinowski (Opuscula Mathematica, 2007)
In the paper the equivalence of the system of two pre-Schröder functional equations (equations \((S_n)\), \((S_m)\) for \(m \gt n ≥ 3\), \(n, m \in \mathbb{N}\)) and the whole system \((S)\), is considered. The results solve the problem of Gy. Targonski [Gy. Targonski, Problem P 63, Aequationes Math. 4 (1970), 251] in a particular case.